Improving Inventory Management and Supply Chain of Diesel Fuel in Pertamina 5 Main Depots - Simatupang, Togar M; Pardhana, Hendra W (The Asian Journal of Technology Management (AJTM), 2010)
Planning Operation subdivision at PT Pertamina has to generate supply decisions includingmain depot to supply, supply point and transportation mode. However, the variability inplanning a supply schedule renders the process of determining a supply decision asineffective. The last assessment on uncertainties was done at 2006 and has not beenconsidered during decision making process. On the other hand, the result of this researchindicates that the uncertainty level is too high to be ignored and the poor informationexchange between the regional offices and the head office decreases the Planning Operation’sability to create plans that covers the company condition. This paper proposes an appropriatesafety stock to withstand the uncertainties and a supply scheduling process that also considersuncertainties by using Monte-Carlo Simulation with random numbers to simulate the events inthe upcoming period.Key words: inventory management, distribution planning, managing uncertainties, montecarlosimulation